Mandatory disclosures and opportunism: Evidence from repurchases - Bratten, Brian; Huang, Meng; Jenkins, Nicole Thorne; Xie, Hong (Journal of Accounting and Economics, 2025)
We examine the effect of disclosure requirements on managers' stock repurchase decisions. In 2003, the SEC amended Rule 10b-18, significantly increasing the disclosure requirements for and transparency of stock repurchases for all issuers. While stock repurchases are often used by firms to efficiently return capital to shareholders, they can also be used opportunistically to increase earnings per share. We find that the 2003 SEC amendment enables investors to detect and discount opportunistic repurchases, curtails the extent to which firms use opportunistic repurchases, and reduces or eliminates the negative real effects stemming from opportunistic repurchases (reduced employment, reduced capital expenditures, and reduced R&D expenditures). Our evidence suggests that disclosures aimed at increasing the transparency of firms’ activities can significantly reduce the extent to which firms use these activities opportunistically to manage earnings, thereby reducing the accompanying real consequences of opportunistic behavior.